Head to head : the coming economic battle among Japan, Europe, and America - Thurow, Lester (New York : Warner Books, 1993)
Originally published: 1st ed. New York: Moscow, 1992
Keywords: Economic forecasting; Economic history -- 1990.; European Economic Community countries -- Economic policy; International economic relations; Japan -- Economic policy; United States -- Economic policy -- 1981.